Influence of saponins and sapogenins on the bacteriolytic activity of ciliate protozoa from the sheep rumen - Teferedegne, B.; Osuji, P.O.; Odenyo, A.A.; Wallace, R.J.; Newbold, C.J. (British Society of Animal Science, 1998)
Foliage from the tropical leguminous tree, Sesbania sesban, is toxic to rumen protozoa in vitro, due to materials present in a saponins-containing extract of the foliage (Newbold et al 1997). Suppression of protozoal numbers in vivo when S. sesban is added to the diet is either transient or non-existent, however, even though washed protozoa remain sensitive to S. sesban in vitro (Newbold et al 1997, Odenyo et al 1997). A possible reason is that saponins are metabolised in rumen fluid (Makkar and Becker 1997). This study determines if the antiprotozoal effect of different accessions of S. sesban was related to their saponins composition, and if conversion of saponins to their sapogenin derivatives was a possible cause of the loss of the antiprotozoal effect in vivo.